Development of Glioblastoma from Stem Cells to a Full-Fledged Tumor - Pavel Vladimirovich NIKITIN; Guzel Railevna MUSINA; Valery Nikolaevich POLOZOV; Dmitry Nikolaevich GOREIKO; Vladimir Mikhailovich KRASNOVSKY; Leonard WERKENBARK; Mauric KJELIN; Piotr Sergeevich TIMASHEV (Federation of Turkish Pathology Societies, 2023)
Objective: IDH wild-type glioblastomas (GBM) are one of the most malignant and complex tumors for treatment. The urgent question of new therapeutic and diagnostic tools searching should be resolved based on cellular and molecular pathogenesis mechanisms, which remain insufficiently studied. In this study, we aimed to investigate GBM pathogenesis. Material and Method: Using the isolation of different GBM cell populations and the cell cultures, animal models, and molecular genetic methods, we tried to clarify the picture of GBM pathogenesis by constructing a projection from different glioma stem cells types to an integral neoplasm. Results: We have shown a potential transformation pathway for both glioma stem cells and four definitive cell populations during gliomagenesis. Moreover, we have characterized each population, taking into account its place in the pathogenetic continuum, with a description of the most fundamental molecular and functional properties. Conclusion: Finally, we have formed a complex holistic concept of the pathogenetic evolution of GBM at the cell-population level by integrating our results with the data of the world literature.